What Factors Can Contribute to Developing Pneumoperitoneum Caused by Sexual Activity? A Case Study - Zsoldos, Márta; Pajor, Attila K. (British Journal of Healthcare and Medical Research, 2022)
Severe abdominal pain caused by pneumoperitoneum extremely rarely occurs in women due to sexual activity. Hence, we report on a unique case with pneumoperitoneum. A 19-year-old Caucasian undergraduate woman had received the third mRNA vaccination against Covid 19 infection. Subsequently, she experienced menstrual disorder during the current and the following cycles. Otherwise, her cycles were previously regular. Just after finishing irregular vaginal bleeding, she had sex with her regular partner in the evening, during which she received oral sex involving blowing air into her vagina and then vaginal intercourse occurred from rear entry. Following coitus, she felt an abrupt sharp pain in the right upper abdominal quadrant, which became permanent and worsened upon moving. She had no gastrointestinal symptoms and fever. She did not want to see a doctor at night, therefore took painkiller and spasmolytic pills. Her pain was gradually decreasing and stopped at dawn. Gynecologic and transvaginal ultrasound exams performed four days later showed retroflected uterus but did not find the reason for pain, however, ten days later an ovarian follicular cyst appeared. Retrospectively, non-surgical pneumoperitoneum was diagnosed which resolved spontaneously. She was unaware of the potential risk of oral sex. This report suggests that the oral sex involving vaginal insufflation and the rear-entry vaginal intercourse may together be predictors of the pneumoperitoneum, and the menstrual disorder likely triggered by the Covid 19 vaccination may be a contributor to its forming.